Culture in Economics history, methodological reflections and contemporary applications - Beugelsdijk, Sjoerd 1976-; Maseland, Robbert Karel Jozef 1975-; Cambridge Books Online (Online service). (Cambridge Cambridge University Press, 2010)
"Many economists now accept that informal institutions and culture play a crucial role in economic outcomes. Driven by the work of economists such as Nobel laureates Douglass North and Gary Becker, there is an important body of work that invokes cultural and institutional factors to build a more comprehensive and realistic theory of economic behavior. This book provides a comprehensive overview of research in this area, sketching the main promises and challenges faced by the field. The first part introduces and explains the various theoretical approaches to studying culture in economics, going back to Smith and Weber, and addresses the methodological issues that need to be considered when including culture in economics. The second part of the book then provides readers with a series of examples that shows how the cultural approach can be used to explain economic phenomena in four different areas: entrepreneurship, trust, international business and comparative corporate governance" -- Provided by publisher
Title from title screen (viewed on November 10, 2023)
Also issued in print format
Mode of access: World Wide Web
Keywords: Economics -- Sociological aspects; Culture -- Economic aspects